Associations Between Complement C4, Habitual Constipation, and Sleep Disturbance in Oldest-Old and Centenarian Chinese Adults - Sun Z; Nie Y; Pei J; Gao M; Luan Z; Zhao Y; Li Z; Fu S (Journal of Inflammation Research)
Zhigao Sun,1,* Yan Nie,2,* Jianqiu Pei,3,* Ming Gao,4,* Zhe Luan,5,* Yali Zhao,6 Zhaoxing Li,7 Shihui Fu8,9 1Traditional Chinese Medicine Department, Hainan Hospital of Chinese People’s Liberation Army General Hospital, Sanya, People’s Republic of China; 2Department of Gastroenterology, Hainan Hospital of Chinese People’s Liberation Army General Hospital, Sanya, People’s Republic of China; 3Department of Biochemistry and Molecular Biology, School of Basic Medical Sciences, Capital Medical University, Beijing, People’s Republic of China; 4School of Engineering Medicine, Beihang University, Beijing, People’s Republic of China; 5Department of Gastroenterology and Hepatology, The First Medical Center of Chinese People’s Liberation Army General Hospital, Beijing, People’s Republic of China; 6Central Laboratory, Hainan Hospital of Chinese People’s Liberation Army General Hospital, Sanya, People’s Republic of China; 7Department of General Surgery, The Fourth Affiliated Hospital of Hebei Medical University, Shijiazhuang, People’s Republic of China; 8Department of Cardiology, Hainan Hospital of Chinese People’s Liberation Army General Hospital, Hainan Geriatric Disease Clinical Medical Research Center, Hainan Branch of China Geriatric Disease Clinical Research Center, Sanya, People’s Republic of China; 9Department of Geriatric Cardiology, Chinese People’s Liberation Army General Hospital, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhaoxing Li, Department of General Surgery, The Fourth Affiliated Hospital of Hebei Medical University, Shijiazhuang, People’s Republic of China, Email lizhaoxing1984@hebmu.edu.cn Shihui Fu, Department of Cardiology, Hainan Hospital of Chinese People’s Liberation Army General Hospital, Hainan Geriatric Disease Clinical Medical Research Center, Hainan Branch of China Geriatric Disease Clinical Research Center, Sanya, People’s Republic of China, Email xiaoxiao0915@126.comBackground: Sleep disturbance is an immune-related disease, and the gut–brain axis is an important regulatory pathway. This cross-sectional study was designed to address these associations between complement C4, habitual constipation, and sleep disturbance and presents a reference for prevention and treatment of sleep disturbance.Methods: Based on the China Hainan Centenarian Cohort Study, Pittsburgh Sleep Quality Index (PSQI) was used to evaluate sleep disturbance following standard procedure. Complement C4 and habitual constipation were assessed between groups with sleep disturbance and without sleep disturbance by enzyme colorimetry and Intestinal Health Questionnaire, respectively.Results: A total of 1621 participants were included with the prevalence of sleep disturbance being 30.41%. Complement C4 was significantly lower (24 mg/dL versus 25 mg/dL, P < 0.05) and habitual constipation was significantly higher (19.88% versus 14.27%, P < 0.05) in the group with sleep disturbance than in the group without sleep disturbance. Multiple linear regression models detected a negative association between complement C4 and PSQI (β: − 0.030, 95% confidence interval [CI]: − 0.052–-0.008, P < 0.05) and a positive association between habitual constipation and PSQI (β: 0.610, 95% CI: 0.145– 1.074, P < 0.05). In the multiple logistic regression models, complement C4 was negatively associated with sleep disturbance (odds ratio: 0.978, 95% CI: 0.963– 0.993, P < 0.05), and habitual constipation was positively associated with sleep disturbance (odds ratio: 1.609, 95% CI: 1.194– 2.168, P < 0.05).Conclusion: The present study provides epidemiological evidence that sleep disturbance is negatively associated with complement C4 and positively associated with habitual constipation in oldest-old and centenarian Chinese adults, which expands the knowledge for the associations between complement C4, habitual constipation, and sleep disturbance in the elderly population and provides new insights and pathways on the treatment of sleep disturbance by regulating immune factors and intestinal function.Keywords: centenarian, complement C4, habitual constipation, oldest-old, sleep disturbance